Studi Kasus Asuhan Kebidanan Komprehensif pada Nyonya M di Klinik Pratama Shaqi, Sleman - Crisma Martadiana; Nining Tunggal Sri Sunarti (Protein : Jurnal Ilmu Keperawatan dan Kebidanan., 2026)
Background: Comprehensive midwifery care is essential for early detection of complications and reducing maternal and infant mortality rates. In Sleman Regency, despite high access to health services, continuous monitoring remains crucial for ensuring maternal and fetal safety. Objective: To provide comprehensive midwifery care for Mrs. M at Klinik Pratama Shaqi, Sleman, from the third trimester of pregnancy through the postpartum and neonatal periods. Methods: This is a descriptive qualitative study using a case study approach based on Varney's seven-step midwifery management and SOAP documentation. Findings: During pregnancy (37 weeks 6 days), the mother experienced physiological complaints of back pain and shortness of breath, managed through posture education and pregnancy exercises. Labor proceeded normally and spontaneously on October 6, 2024, utilizing "gentle birth" practices such as endorphin massage to reduce pain. A second-degree perineal tear occurred and was treated according to procedure. The baby was born healthy, weighing 3100 grams, with successful Early Initiation of Breastfeeding (EIB). During the postpartum and neonatal periods, uterine involution was normal, breast milk production was adequate, and the infant's growth met standards with no danger signs. Implications: Continuous assistance improves the mother's physical and psychological readiness and ensures a healthy neonatal transition.